Pengelolaan Persediaan Jasa: Suatu Contoh Aplikasi pada Jasa Rumah Sakit - Cecep Hidayat (Bina Nusantara University, 2012)
The services sector contribute more than 70% of gross domestic product (GNP) almost all countries in the world, even the more advanced the countries are the more contribution the countries will give. Services inventory means that complementary service inventories, both human beings and machines, as well as goods and equipment that accompany delivery of services.Inventory models for services haven’t been specific, but basically they are almost similar to the inventory model for the product in the form of goods. The hospital are the places of business that produce services, so that the logistic of hospital is not the logistics of goods distribution, but it is only about material goods inventory management and equipment needed to produce those services. The most aplicable inventory services for hospital are the ABC classification model.